La doctrina tomista de la ley natural en el marco de la participación del hombre en la providencia divina. - Martín, Manuel (Humanidades: Revista de la Universidad de Montevideo)
In this paper I examine the nature of natural law according to Thomas Aquinas in the context of man's participation in Divine Providence. I argue that God gives the law to man to guide him in his personal actions, but that He gives it in such a way that man precepts it to govern himself and other things, and thus to come to resemble the provident God. To do this, I first explain man's special participation in Divine Providence. Second, I examine St. Thomas' claim that God gives laws to man. Third, I relate this to the claim that the natural law is a participation of the eternal law in us. Finally, I argue that God is the author of the law, but that He establishes it in such a way that man gives it to himself by participation.